A Stimulated Recall Method for the Improved Assessment of Quantity and Quality of Social Media Use - Griffioen, Nastasia; Van Rooij, Marieke M J W; Lichtwarck-Aschoff, Anna; Granic, Isabela (JMIR Publications, 2020)
BackgroundSocial media are as popular as ever, and concerns regarding the effects of social media use on adolescent well-being and mental health have sparked many scientific studies into use effects. Social media research is currently at an important crossroads: conflicting results on social media use's effects on well-being are abundant, and recent work in the field suggests that a new approach is required. The field is in need of an approach involving objective data regarding use where necessary and attention to different kinds of detail such as the why and how of social media use. ObjectiveWe present a novel paradigm implementing a principle from educational sciences called stimulated recall and demonstrate how it can be applied to social media use research. Our stimulated recall paradigm implements a number of elements that can fill the gaps currently present in social media and well-being research. MethodsObjective data are collected regarding users' social media behaviors through video footage and in-phone data and used for a structured stimulated recall interview to facilitate detailed and context-sensitive processing of these objective data. In this interview, objective data are reviewed with the participant in an act of co-research, in which details such as the reasons for their use (eg, boredom) and processes surrounding their use (eg, with whom) are discussed and visualized in a stimulated recall chart. ResultsOur ongoing study (N=53) implementing this paradigm suggests this method is experienced as pleasant by participants in spite of its personal and intensive nature. ConclusionsThe stimulated recall paradigm offers interesting and necessary avenues for approaching social media use research from new angles, addressing aspects of use that have thus far remained underexposed. The answers to questions such as "Why do adolescents use social media?" "In what ways exactly do they use social media?" and "How does social media use make them feel in the moment?" are now within reach, an important step forward in the field of social media use and well-being research.